Why punish perpetrators of mass atrocities?: purposes of punishment in international criminal law - Jeßberger, Florian; Geneuss, Julia (Asil studies in international legal theory, 2020)
"Why punish perpetrators of mass atrocities? Given the rapid development and advancing consolidation of international criminal law it seems rather late to ask this question. However, the question of rationales of international punishment is still under-researched and under-theorized, and of relevance for a solid grounding of international criminal law. Therefore, in our view, it was about time to bring together scholars and practitioners from different disciplines and groups of experts: scholars whose research focuses on theories of punishment in general, scholars whose main research interest is international criminal law, and finally lawyers working at international criminal courts or tribunals and concerned with the enforcement of international criminal law. The present volume is the result of these discussions"--